2022
DOI: 10.5114/fn.2022.118184
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates autophagy and inflammation after traumatic brain injury by activation of PI3K/Akt/mTOR pathway in rats

Abstract: Aim of the study: Accumulating studies have demonstrated that neuronal autophagy and inflammation are crucial for hippocampus development in rats subjected to traumatic brain injury (TBI). Therefore, we have investigated whether resveratrol is protective against brain damage through the attenuation of neuronal autophagy and inflammation, and explored underlying mechanisms. Material and methods: Rats were injected with resveratrol (50 mg/kg, i.p.), following controlled cortical impact (CCI) injury. Brain water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Notably, phagosome formation and autophagy, specifically, are among the most significantly affected signaling pathways in thymus extract‐supplemented animals (Figure 4). Autophagy is vital for both the pathogenesis and the recovery from TBI and can also be triggered by nutrient deprivation and attenuated by nutrient supplementation 88,101–104 . On the one hand, increased autophagy following TBI can be beneficial for converting damaged or dysfunctional molecules and cellular organelles into their recyclable components.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, phagosome formation and autophagy, specifically, are among the most significantly affected signaling pathways in thymus extract‐supplemented animals (Figure 4). Autophagy is vital for both the pathogenesis and the recovery from TBI and can also be triggered by nutrient deprivation and attenuated by nutrient supplementation 88,101–104 . On the one hand, increased autophagy following TBI can be beneficial for converting damaged or dysfunctional molecules and cellular organelles into their recyclable components.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is vital for both the pathogenesis and the recovery from TBI and can also be triggered by nutrient deprivation and attenuated by nutrient supplementation. 88,[101][102][103][104] On the one hand, increased autophagy following TBI can be beneficial for converting damaged or dysfunctional molecules and cellular organelles into their recyclable components. On the other hand, prolonged autophagy can also eliminate functional proteins, lipids, nucleic acids, and cellular organelles.…”
Section: Serum Igg Levels Correlate With Vestibulomotor Function Reco...mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, trans-resveratrol has demonstrated anti-tumor, anti-oxidation, anti-inflammatory, and other effects. 41 Studies indicated that trans-resveratrol attenuated inflammation and oxidative stress by reducing the expression of IL1B, 42 GAPDH, 43 and VWF. 44 Trans-resveratrol also inhibited the metastasis of LUAD by inhibiting NF-κB pathway mediated by heme oxygenase-1 (HO-1) and down-regulating MMP9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant effect is largely related to the activation of the PI3K/Akt-mediated Nrf2 pathway by resveratrol, ref. [ 5 ] and its antitumor effect is achieved through regulation of the PI3K/Akt/mTOR pathway [ 6 ]. Resveratrol modulates apoptosis, mediated by the Fas/Fas ligand, p53 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%